Use of Encapsulated Garlic Oil in Low-Fat Salad Dressings: Physicochemical, Microbial and Sensory Properties - Khoshtinat, Khadijeh; Barzegar, Mohsen; Sahari, Mohammad Ali; Hamidi, Zohreh (Applied Food Biotechnology, 2022)
Background and Objective: Fresh garlic includes several preservative and medicinal characteristics; however, its major bioactive components react and convert to other chemical compounds as soon as its tissues are injured. Garlic oil is extracted from garlic and its use in food industries is limited due to its strong odor, taste, volatility and low solubility in aqueous solvents. The aim of the present study was to investigate physicochemical, microbial and sensory properties of low-fat salad dressings containing encapsulated garlic oil in ß-cyclodextrin (GO/ß-CD). Material and Methods: Five types of salad dressing, including control with no garlic oil, a sample with free garlic oil and three samples containing 546, 818 and 1364 mg GO/ß-CD kg-1 salad dressing were prepared. Then, pH, color and antioxidant [(peroxide value and thiobarbituric acid reactive substances], antimicrobial (monitoring of four pathogens of Bacillus cereus, Staphylococcus aureus, Escherichia coli and Salmonella enterica) and sensory (taste, color, odor and acceptability by 8-point hedonic test) properties of the samples were assessed during 41 days of storage at 4 oC. Results and Conclusion: The minimum and the maximum color differences belonged to GO/ß-CD-3 sample containing 1364 mg GO/ß-CD kg-1 salad dressing and sample containing free GO, respectively. Yellowness of samples containing encapsulated GO decreased and direct relationships were seen between decreasing of the sample yellowness and quantity of GO/ß-CD sample. During the storage, pH and peroxide value PV slightly increased. Staphylococcus aureus was the most sensitive strain to free and encapsulated garlic oil. Escherichia coli, Salmonella enterica and Bacillus cereus showed lower sensitivities to the oil. Sensory results showed no significant differences between the tastes of control and free or encapsulated garlic oil and GO/ß-CD-2 samples containing 818 mg kg-1 encapsulated garlic oil, equal to 90 mg kg-1 free garlic oil. However, these two treatments included significant differences with samples containing free garlic oil. Results revealed that encapsulation of garlic oil with ß-CD included no adverse effects on taste of the salad dressings. Therefore, GO/ß-CD-2 (818 mg GO/ß-CD kg-1 salad dressing) can be suggested as a natural antimicrobial agent for the functional mayonnaise production. Conflict of interest: The authors declare no conflict of interest.